2014
DOI: 10.4314/ejhs.v24i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Antiplaque Efficacy of <i>Aloe Vera</i> Mouthwash on 4 Day Plaque Re -Growth Model: Randomized Control Trial

Abstract: BackgroundPalmaris longus, being the most variable muscle of the upper extremity is generally considered important morphologically rather than functionally. The palmar aponeurosis represents the distal part of the tendon of Palmaris longus.Case DetailsWe report here a unique case of palmaris longus presenting variation distally as its tendon divides to gain multiple attachments with the fascia covering the abductor pollicis brevis, flexor retinaculum and the tendon of flexor carpi ulnaris. In addition, it also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
4
27
0
3
Order By: Relevance
“…A randomized controlled study using 100% aloe vera extract showed significant reduction in plaque formation with no reported side effects. 64 Similar observations were found in other studies. 65 The antimicrobial effect of aloe vera has been demonstrated earlier in an in vitro study.…”
Section: Aloe Vera Extractsupporting
confidence: 89%
“…A randomized controlled study using 100% aloe vera extract showed significant reduction in plaque formation with no reported side effects. 64 Similar observations were found in other studies. 65 The antimicrobial effect of aloe vera has been demonstrated earlier in an in vitro study.…”
Section: Aloe Vera Extractsupporting
confidence: 89%
“…The gold standard material in chemical plaque control is chlorhexidine. Nevertheless, this substance cannot be used for long periods due to its side effects, such as unusual or unpleasant taste in mouth, tooth/tongue staining, and increased calculus formation [5]. Considering the side effects of chemical mouthwash, there has been a growing interest in using herbal agents with antimicrobial and anti-inflammatory properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fani and Kohanteb also found that the optimal dose of aloe vera in toothpaste and mouthwash had preventive effects on tooth decay and periodontal disease [8]. Moreover, Kumar and co-workers showed no significant difference in the anti-plaque effects of aloe vera mouthwash and chlorhexidine 0.2% [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common gingivitis is caused by bacteria found in plaque and calculus and can only be mechanically removed (toothbrush), chemically (toothpaste and mouthwash), physical intervention (scaling and root planning) or even a combination of all three in some cases [6,7]. But nowadays people tend to prefer herbal ingredients one of them is mouthwash from Aloe vera because in addition to its safe materials contained, it is also economical and easy to obtain, this material also has no side effect to its user, but still effective in reducing bacteria causing plaque [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Aloe vera has been tested in reducing plaque formation in the oral cavity, active components of Aloe vera gel such as aloe, aloe-emodin, aloemannan, acemannan, aloeride, naftoquinones, flavonoids, saponins, sterols, Amino acids and vitamins are proven to be beneficial to oral health [8]. Some authors found that mouth rinse containing Aloe vera was equally effective in reducing plaque formation with chlorhexidine for 4 days of observation, in addition to Aloe vera mouth rinse also had no side effects [8].…”
Section: Introductionmentioning
confidence: 99%